Effects of late exercise on cardiac remodeling and myocardial calcium handling proteins in rats with moderate and large size myocardial infarction - Guizoni, Daniele M. [UNESP]; Oliveira-Junior, Silvio A.; Noor, Sefora L.R. [UNESP]; Pagan, Luana U. [UNESP]; Martinez, Paula F. [UNESP]; Lima, Aline R.R. [UNESP]; Gomes, Mariana J. [UNESP]; Damatto, Ricardo L. [UNESP]; Cezar, Marcelo D.M. [UNESP]; Bonomo, Camila [UNESP]; Zornoff, Leonardo A.M. [UNESP]; Okoshi, Katashi [UNESP]; et al. (Elsevier, 2016)
Background Physical exercise attenuates myocardial infarction (MI)-induced cardiac remodeling. However, it is unsettled whether late exercise modulates post-infarction cardiac remodeling differentially according to infarct size. We investigated the effects of exercise started at late stage heart failure on cardiac remodeling in rats with moderate and large sized MI. Methods Three months after MI, rats were assigned into sedentary and exercise groups. Exercise rats underwent treadmill for three months. After assessing infarct size by histological analysis, rats were subdivided into four groups: moderate MI sedentary (Mod MI-Sed; n = 7), Mod MI exercised (Mod MI-Ex; n = 7), Large MI-Sed (n = 11), and Large MI-Ex (n = 10). Results Before exercise, MI-induced cardiac changes were demonstrated by comparing results to a Sham group; alterations were more intense in rats with large than moderate MI size. Systolic function, evaluated by echocardiogram using the variation in LV fractional area change between after and before exercise, was improved in exercise than sedentary groups. Calsequestrin expression increased in exercised compared to sedentary groups. L-type calcium channel was higher in Mod MI-Ex than Mod MI-Sed. SERCA2a, phospholamban, and Na+/Ca2 + exchanger expression did not differ between groups. Conclusion Late exercise improves systolic function and modulates intracellular calcium signaling proteins in rats with moderate and large MI.
Keywords: Calsequestrin; Cardiac function; Echocardiogram; Myocardial infarction; Physical exercise; Remodeling